2023
DOI: 10.1038/s41598-023-32831-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the norm activation model and theory of planned behaviour to investigate farmer pro-environmental behavioural intention

Abstract: Sustainable agriculture requires cooperative and coordinated action across multiple sectors and policy domains. However, farmer-stakeholder behaviors and action remain pivotal to sustainable food system management in many rural development contexts. We assess farmer pro-environmental behavioral intention through the development and application of a novel integrated approach combining two dominant psychological theories of behavior change: the Norm Activation Model (NAM) and Theory of Planned Behavior (TPB). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…Attitude has the greatest impact on farmers' intentions to adopt GCT, which is consistent with the research of Asante et al [77] and Despotovic et al [24], indicating that the higher the farmers' recognition of the consequences of the adoption of GCT, the stronger their intentions to adopt. Subjective norm is the second major factor affecting adoption intentions, which is consistent with the research of Damalas [42] and Savari et al [78]. Since the current adoption of GCT is still a government-led activity, the government provides skills training and subsidies to farmers through joint cooperatives or agricultural enterprises.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Attitude has the greatest impact on farmers' intentions to adopt GCT, which is consistent with the research of Asante et al [77] and Despotovic et al [24], indicating that the higher the farmers' recognition of the consequences of the adoption of GCT, the stronger their intentions to adopt. Subjective norm is the second major factor affecting adoption intentions, which is consistent with the research of Damalas [42] and Savari et al [78]. Since the current adoption of GCT is still a government-led activity, the government provides skills training and subsidies to farmers through joint cooperatives or agricultural enterprises.…”
Section: Discussionsupporting
confidence: 81%
“…Perceived behavioral control has a positive impact on farmers' adoption intentions, and studies by Rezaei ea al. [25], Lou et al [26], and Savari et al [78] support this conclusion. Farmers' perceived behavioral control over the adoption of GCT mainly depends on their perception of resources, such as knowledge and skills, time and energy, and technical payment capabilities [25], which means that when farmers lack the perception of these resources, they will likely reduce their intentions to adopt GCT.…”
Section: Discussionmentioning
confidence: 86%
“…The analysis of construct cross-validated redundancy is shown in Table 6. The findings of construct cross-validated redundancy showed that measured values for Q 2 are greater than zero, which ensures that the predictive relevance of the model is significant [32]. Moreover, it can also be seen that predictive relevance for community development is lesser than the use of biofertilizers.…”
Section: Predictive Relevancementioning
confidence: 85%
“…The theory of planned behavior (TPB) has been widely used to examine various aspects of people, such as to predict organic food adoption behavior ( 22 ), dietary behaviors ( 23 ), also to predict sugar intake ( 24 ), the intention to adopt a healthy diet ( 25 ) and fast food consumption ( 26 ); furthermore, its application has also been transferred to other contexts such as oral health behaviors ( 27 ), improving medication adherence ( 28 ), teaching complementary medicine ( 29 ), pro-environmental behavioral intention ( 30 ) and understanding Facebook user behavior ( 31 ). In this sense, the TPB is used to understand and predict human behavior, particularly in decision-making associated with planned actions or behaviors ( 22 ).…”
Section: Introductionmentioning
confidence: 99%